2016
DOI: 10.1007/s12663-016-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Superolateral Dislocation of Bilateral Intact Mandibular Condyles: A Rare Case Series

Abstract: This article intends to provide information regarding the possible biomechanics and management of bilateral superolateral dislocation of mandibular condyles associated with symphysis fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They reported that 33.9% of females and 24.6% of males had systemic ailments. Another study [19] also reported no association between gender and neurological, hepatobiliary and psychological diseases but found a higher prevalence of cardiovascular, respiratory, autoimmune, gastrointestinal and endocrine diseases in females. According to our study, a significant association was found between the age of patient and the type of minor oral surgery with maximum procedures performed (37.4%) for patients in the 21-30 years age group.…”
Section: Discussionmentioning
confidence: 93%
“…They reported that 33.9% of females and 24.6% of males had systemic ailments. Another study [19] also reported no association between gender and neurological, hepatobiliary and psychological diseases but found a higher prevalence of cardiovascular, respiratory, autoimmune, gastrointestinal and endocrine diseases in females. According to our study, a significant association was found between the age of patient and the type of minor oral surgery with maximum procedures performed (37.4%) for patients in the 21-30 years age group.…”
Section: Discussionmentioning
confidence: 93%
“…Of the 16 publications reviewed, 12 (75%) were Indian (Tab. II) [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. 30 patients were involved with a mean age of 31.87 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The average treatment time was 11.78 days (Tab. II) [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anterior and medial condyle dislocations commonly occur due to the pull of the lateral pterygoid muscle, while superior and lateral condyle dislocations occur less frequently 1 . Superolateral condyle dislocation has been rarely reported because the mandibular condyle is surrounded by the temporomandibular joint (TMJ) structure including the capsule, ligament, disc, and masticatory muscles 2,3 . Lateral condyle dislocations were classified by Allen and Young 4 as Type I, which is a lateral subluxation, and Type II, which is complete dislocation of the condyle from the glenoid fossa.…”
Section: Introductionmentioning
confidence: 99%